Microstructure and compressive/tensile characteristic of large size Zr-based bulk metallic glass prepared by laser solid forming. Issue 2 (February 2019) - Lin, Xin; Zhang, Yuanyuan; Yang, Gaolin; Gao, Xuehao; Hu, Qiao; Yu, Jun; Wei, Lei; Huang, Weidong
Abstract: The large size, crack-free Zr55 Cu30 Al10 Ni5 bulk metallic glass (BMGs) with the diameter of 54 mm and the height of 15 mm was built by laser solid forming additive manufacturing technology, whose size is larger than the critical diameter by casting. The microstructure, tensile and compressive deformation behaviors and fracture morphology of laser solid formed Zr55 Cu30 Al10 Ni5 BMGs were investigated. It is found that the crystallization mainly occurs in the heat-affected zones of deposition layers, which consist of Al5 Ni3 Zr2, NiZr2, ZrCu, CuZr2 phases. The content of amorphous phase in the deposit is about 63%. Under the compressive loading, the deposit presents no plasticity before fracture occurs. The fracture process is mainly controlled by the shear stress and the compressive shear fracture angles of about 39°. The compressive strength reaches 1452 MPa, which is equivalent to that of as-Cast Zr55 Cu30 Al10 Ni5 BMGs, and there exist vein-like patterns, river-like patterns and smooth regions at the compressive fractography. Under the tensile loading, the deposit presents the brittle fracture pattern without plastic deformation. The fracture process exhibits normal fracture model, and the tensile shear fracture angle of about 90°. The tensile strength is only about 609 MPa, and the tensile fractography mainly consists of micro-scaled cores and vein-like patterns, dimple-like patterns, chocolate-like patterns and smooth regions. The results further verified the feasibility and large potential of laser additive manufacturing on fabrication and industrial application of large-scale BMGs parts.